IMPLEMENTASI LATIHAN FLEKSI WILLIAM PADA GAMBARAN KARAKTERISTIK NYERI PUNGGUNG BAWAH LANSIA DENGAN RHEMATOID ARTHRITIS (RA) DI UPT PELAYANAN SOSIAL LANJUT USIA BINJAI - Daulay, Amanda Ulfa Hawari; Pratama, Muchti Yuda; Olivia, Nina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Rheumatoid Arthritis (RA) in the elderly is a chronic systemic autoimmune disease that causes inflammation of connective tissue, primarily in the joints. Common complaints among patients include lower back pain and mobility disorders. William's flexion exercise is a stretching technique targeting body muscles to promote relaxation, increase range of motion, provide comfort, and help prevent injuries. This study aims to describe the implementation of William's flexion exercise for reducing lower back pain in elderly patients with RA. The research method used is descriptive, presented in the form of a scientific paper with a nursing care approach, starting from assessment, diagnosis, intervention, implementation, and evaluation. The nursing care plan instrument was based on the Indonesian Nursing Intervention Standards (SIKI, 2018). This study involved two elderly RApatients who experienced mild to severe lower back pain. William's flexion exercise was implemented for 30 minutes over six days. The results showed a reduction in lower back pain, from moderate to mild pain levels. In conclusion, the implementation of William's flexion therapy demonstrated a decrease in the painscale among elderly patients with RA. It is recommended that this intervention be developed into a Standard Operating Procedure (SOP) for managing lower back pain in elderly RA patients in geriatric care units.